Exogenous Application of Melatonin and Methyl Jasmonate as a Pre-Harvest Treatment Enhances Growth of Barhi Date Palm Trees, Prolongs Storability, and Maintains Quality of Their Fruits under Storage Conditions - Waleed M. E. Fekry; Younes M. Rashad; Ibrahim A. Alaraidh; Taha Mehany (Plants, 2021)
Fresh date palm fruits (cv. Barhi) have received much attention due to their sweet taste and popularity in marketing. There is a critical need to prolong their storability, as well as maintain their quality during the postharvest and marketing periods. In this study, the effects of spraying date palm trees with melatonin (Mt) and/or methyl jasmonate (Mj) at 10, 20, and 50 ppm, on their growth and yield were investigated. In addition, impacts on quality and storability of the fruits were also studied. In general, application of Mt was mostly more effective than that of Mj, even at 50 ppm, with regard to all evaluated parameters. However, the dual treatment at 50 ppm recorded the highest relative chlorophyll and nutrient content in date palm leaves, as well as the yield and its components. Regarding the date palm fruits stored at 4 °C for 28 days, this dual treatment recorded the lowest weight loss and fruit decay values (0.14 and 2%, respectively), the highest firmness (6 g·cm−2), total soluble solids content (36 °Brix), total sugar content (32.5 g/100 g fresh weight), and the lowest total acidity (0.16 g citric acid/100 mL juice). Moreover, the highest total phenolic content and activity of peroxidase and polyphenol oxidase enzymes in the stored fruits were also recorded for the dual treatment. In contrast to the untreated fruits, scanning electron microscopy observations showed that the sprayed fruits had a very good microstructure, showing intact and thick exocarp tissue with a dense layer of epicuticular wax. The mesocarp tissue showed a normal and clear cellular framework with well organized and arranged cells, after 28 days storage at 4 °C. Based on these results, we can conclude that application of the dual treatment (Mt + Mj) at 50 ppm is a promising way to prolong the storability of date palm fruits and maintain their quality during storage periods.